CONCEPT-MODEL OF SEMI-DUPLEX VHF TRAINING STATION - Bogunenko, Mykola; Luppo, Oleksandr; Argunov, Gennadiy; Subbotin, Serhii; German, Alina (Proceedings of National Aviation University (archive), 2019)
The article is devoted to the elaboration of improvement communication systems of existing aviation simulators. Extra VHF semi-duplex communication units simulate operation like in real condition. Authors developed and produced principal layout of PTT module for improvement aviation personal skills.